A multi-objective programming model based on the relative deviation - Wu, Xinlin; Xu, Min (Journal of physics. Conference series, 2021)
Decision makers are often faced with the achievement of multiple goals in real life. The multi-objective programming model based on priority factors is an effective mathematical model to deal with multiple objectives, but it has some defects. In this paper, the concept of the relative deviation is introduced to deal with the defects of the multi-objective programming model based on priority factors, and the multi-objective programming model based on the relative deviation is proposed. A case study of portfolio decisions is given to illustrate the model. Results show that the model in this paper has more advantages than the traditional model based on priority factors.